Application of PCR-RFLP technique and direct PCR-sequencing analysis to determine the relationships of Acanthamoeba - Manaf, Siti Ruhaya Abdul; Amin, Nakisah Mat; Ali, Abdul Manaf (Penerbit Universiti Sains Malaysia, 2004)
The genus of Acanthamoeba comprises of several free-living amoebae and mostly found in environment habitats worldwide. These organisms can infect a variety of mammals, including humans involving brain, eyes, skin, bones and lungs (Armstrong, 2000; Martinez, 1999). The taxonomy of Acanthamoeba is has yet to be established and still under review, although species identification of the genus by cyst morphology has been extensively used (Page, 1967).